The scope and regioselectivity of intramolecular N-C rearrangements of orthogonally protected sulfonamides, including cyclization to saccharin derivatives. Issue 32 (9th August 2017) - Saidykhan, Amie; Ebert, Jenessa; Ally, Hashim; Gallagher, Richard T.; Martin, William H.C.; Bowen, Richard D.
Graphical abstract: Highlights: The rearrangement can tolerate acidic protons. In sterically demanding substrates the saccharine is formed directly. The rearrangement of naphthalene derivatives is regioselective. Abstract: The scope and regiochemistry of the intramolecular N-C rearrangement involving ortholithiation of orthogonally protected sulfonamides in which an N-acyl or N-carboalkoxy group is transferred from nitrogen to the aromatic ring have been explored. Provided that excess lithium diisopropylamide is used, the process is compatible with the presence of acidic α-protons in a substituent attached to the aromatic ring or if the protons in the migrating acyl group are relatively inaccessible because of steric factors. In certain cases, the isolated product is not the ortho carboalkoxy species, but the derived saccharin; the regiochemistry found for starting materials containing a naphthalene ring is consistent with ortho lithiation at the most electron deficient position.